Complete genome sequence of Mycoplasma mycoides subsp. mycoides T1/44, a vaccine strain against contagious bovine pleuropneumonia - Gourgues, G.; Barre, A.; Beaudoing, E.; Weber, J.; Magdelenat, G.; Barbe, V.; Schieck, Elise G.; Jores, Joerg; Vashee, S.; Blanchard, Alain; Lartigue, C.; Sirand-Pugnet, P. (American Society for Microbiology, 2016)
Mycoplasma mycoides subsp. mycoides is the etiologic agent of contagious bovine pleuropneumonia. We report here the complete genome sequence of the strain T1/44, which is widely used as a live vaccine in Africa.